Effectiveness of Surgical Treatment for Degenerative Cervical Myelopathy in Preventing Falls and Fall-related Neurological Deterioration: A Prospective Multi-institutional Study. Issue 11 (1st June 2020) - Kimura, Atsushi; Takeshita, Katsushi; Shiraishi, Yasuyuki; Inose, Hiroyuki; Yoshii, Toshitaka; Maekawa, Asato; Endo, Kenji; Miyamoto, Takuya; Furuya, Takeo; Nakamura, Akira; Mori, Kanji; Seki, Shoji; et al.
Abstract : Study Design: Prospective multi-center study. Objective: The aim of this study was to evaluate the effectiveness of surgical treatment in reducing falls and fall-related neurological deterioration in a prospective cohort of patients undergoing surgery for degenerative cervical myelopathy (DCM). Summary of Background Data: Current evidence is limited for the effectiveness of surgical interventions for DCM in reducing the risk of fall-related neurological deterioration. Methods: Patients with DCM scheduled for surgical treatment were enrolled prospectively at eight participating institutes. At the time of enrollment, participants were given diaries to record details of their falls, to be returned at the 1-year postoperative follow-up. In the fall diary, patients were asked whether they had experienced any deterioration in neurological symptoms at each fall episode. Deterioration of neurological symptoms was categorized as follows: only deterioration of sensory function in the limbs; or deterioration of motor deficits. The incidence rate of falls was calculated separately for the preoperative and postoperative periods, as the total number of falls divided by the time over which falls were monitored (100 person-years). Functional outcome was assessed with the Japanese Orthopaedic Association (JOA) score and Neck Disability Index. Results: Of the initial 168 participants, 159 completed the 1-year follow-up, and 132 fall diaries were retrieved and analyzed. Of these 132 patients, 65 (49%) reported at least one fall during the survey period. The incidence rate of falls decreased significantly from 497.4 to 90.3 falls per 100 person-years after surgery. The incidence of motor deterioration per fall decreased significantly from 34% to 8% after surgery. Patients who experienced preoperative fall-related motor deterioration had a significantly lower JOA score compared with patients without fall-related motor deterioration at 1-year follow-up. Conclusion: Surgical intervention for DCM is effective not only in reducing the frequency of falls, but also in reducing the risk of fall-related deterioration of motor deficits. Level of Evidence: 2 Abstract : We conducted a prospective multi-institutional study to evaluate the effectiveness of surgical interventions in reducing the risk of fall-related neurological deterioration in patients with degenerative cervical myelopathy. Surgical treatment significantly reduced not only the frequency of falls, but also the risk of fall-related deterioration of motor deficits.